The role of powered instrumentation in the removal of antrochoanal polyps: a 10-Year Review - Mohd Tahir J,; Gendeh BS,; Mohd Razif MY, (Penerbit UKM, 2009)
Antrochoanal polyps are rare lesions. We report a series of 40 consecutive cases of antrochoanal polyps treated in our tertiary centre over a period of ten years between May 1998 and April 2008. The median age of the patients was 37 years. The most common clinical symptom was nasal obstruction (92.5%) followed by rhinorrhoea (45%), postnasal drip (35%) and snoring (22.5 %). The median period of follow-up of these patients was 30 months. Various surgical approaches were used; the commonest was powered endoscopic polypectomy and middle meatal antrostomy in 28 patients (70%), followed by endoscopic polypectomy and middle meatal antrostomy in seven patients (17.5%). Five patients (12.5%) underwent powered endoscopic polypectomy without middle meatal antrostomy. In addition, two patients had septoplasty and one had a frontal sinustomy. There were six patients (15%) who had combined sublabial antrostomy. No major complications occurred; four patients relapsed; three patients had initial operation performed elsewhere and one patient developed recurrence after the first surgery. The median hospitalization period was three days. We conclude that, the use of powered instrumentation in the removal of antrochoanal polyps is safe, effective and associated with minimal morbidity.